Extraction and trapping of truffle flavoring compounds into food matrices using supercritical CO2. (February 2023) - Tejedor-Calvo, Eva; Marco, Pedro; Spègel, Peter; Soler-Rivas, Cristina
Graphical abstract: Highlights: SFE-CO2 (30 MPa, 82.5 min) generated flavoring fractions from truffles. Trapping material placed at the SFE outlet enhanced capture sterols and fatty acids. A total of 32 metabolites were detected by UHPSFC-QTOF-MS. Abstract: A supercritical fluid extraction methodology was used to extract flavoring and bioactive compounds from truffles. Some parameters such as CO2 flow rate (1–3 mg/mL), extraction time (15–90 min) and different trapping food matrices (grape seed oil, gelatin, agar agar and water) were optimized using response surface methodology to enhance extraction and trapping yields. The optimal conditions (2.27 mg/mL CO2 flow rate, 82.5 min when using 40 °C and 30 MPa, with 1 mL grape seed oil as trapping matrix) obtained with Tuber melanosporum were applied to three different truffle species: Terfezia claveryi, Tuber aestivum and Tuber indicum . A total of 32 metabolites were profiled in the extracts using ultra-high-performance supercritical fluid chromatography coupled to quadrupole time-of-flight mass spectrometry. Compounds such as brassicasterol ergosta-7, 22-dienol, oleic and linoleic acid were found at similar amounts in all the extracts but other molecules ( e.g. fungal sterols) showed a particular distribution depending on the specie studied and whether a trapping matrix was used at the SFE outlet.